Effect of auricular acupoint massage combined with auricular acupoint pressing in nursing of patients with insomnia of heart and spleen deficiency type (耳穴按摩操联合耳穴压丸缓解心脾两虚型失眠效果观察) - LI Chunhong (李春红) (中西医结合护理)
Objective To observe the effect of auricular acupoint massage combined with auricular acupoint pressing in nursing of patients with insomnia of heart and spleen deficiency type. Methods A total of 108 inpatients diagnosed with insomnia of heart and spleen deficiency type in the Acupuncture Department of the hospital from August 2022 to July 2023 were selected and divided into a control group and an observation group, with 54 cases in each group according to the order of admission. Both groups received routine treatment and nursing care. The control group underwent auricular acupoint pressing therapy, while the observation group received auricular acupoint massage combined with auricular acupoint pressing therapy. The massage exercises were performed once daily for one week per course, with two courses (two weeks) in total. Changes in Pittsburgh Sleep Quality Index (PSQI) scores before and after the intervention were compared between two groups. Results After the intervention, significant improvements were observed in PSQI scores in both groups(P＜0. 05). Better measurement outcomes in assessment of sleep latency, habitual sleep efficiency, subjective sleep quality, sleep duration, daytime dysfunction and sleep disorders were observed in the observation group compared with those in the control group (P＜0. 05). Conclusion The combination of auricular acupoint massage combined with auricular acupoint pressing therapy in nursing of patients with insomnia of heart and spleen deficiency type effectively improves PSQI symptom scores. This approach not only leverages the advantages of external therapy in traditional Chinese medicine but also alleviates patients' discomfort and enhances their sleep quality. (目的 观察耳穴按摩操联合耳穴压丸缓解心脾两虚型失眠的效果。方法 选取院内针灸科病房2022年8月—2023年7月住院且辨证为心脾两虚型失眠的患者共108例, 根据入院顺序分为对照组和观察组, 各54例。两组患者均采用常规治疗及护理。对照组采用耳穴压丸治疗; 观察组在对照组耳穴压丸治疗的基础上增加耳穴按摩操, 每日做按摩操1次, 1周为1个疗程, 2个疗程(2周)后对比两组患者干预前后匹兹堡睡眠质量指数(PSQI)评分改变状况。结果 干预后, 两组PSQI量表总分和各因子评分均较治疗前下降(P＜0. 05); 观察组入睡时间、睡眠效率、主观睡眠质量、睡眠时间、日间功能和睡眠障碍因子评分较对照组改善明显, 差异有统计学意义(P＜0. 05)。结论 将耳穴按摩操联合耳穴压丸治疗应用于心脾两虚型失眠患者护理中, 能有效改善患者不适症状, 提高患者的睡眠质量, 发挥了中医外治疗法的优势)